2022
DOI: 10.1155/2022/2676367
|View full text |Cite
|
Sign up to set email alerts
|

Unicystic Mucoepidermoid Carcinoma: A Pitfall for Clinical and Pathologic Diagnosis

Abstract: Unicystic mucoepidermoid carcinoma (UC-MEC) is a rare MEC variant, and its diagnosis is frequently problematic. This study is aimed at summarizing its clinicopathologic characteristics, treatment, and prognosis and proposing key points to avoid missed diagnosis and misdiagnosis in clinical and pathological conditions. This retrospective study included 30 UC-MEC cases, and the clinical findings were collected from the clinical medical records. Radiographic features, histologic behaviors, MAML2 rearrangement by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…MAML2 rearrangement in MEC is not specific to salivary gland origin, as MEC of other origins, such as thymus, lung, lacrimal gland, and uterine cervix, have also demonstrated MAML2 rearrangement [25][26][27][28]. Our literature review only identified nine reports/studies documenting the presence of MAML2 rearrangement in CMEC in 30 cases (Table 1) [10][11][12][13][14][15][16][17][18]. Of these, site and demographic information are provided for 25 cases [10,11,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MAML2 rearrangement in MEC is not specific to salivary gland origin, as MEC of other origins, such as thymus, lung, lacrimal gland, and uterine cervix, have also demonstrated MAML2 rearrangement [25][26][27][28]. Our literature review only identified nine reports/studies documenting the presence of MAML2 rearrangement in CMEC in 30 cases (Table 1) [10][11][12][13][14][15][16][17][18]. Of these, site and demographic information are provided for 25 cases [10,11,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review only identified nine reports/studies documenting the presence of MAML2 rearrangement in CMEC in 30 cases (Table 1) [10][11][12][13][14][15][16][17][18]. Of these, site and demographic information are provided for 25 cases [10,11,[13][14][15][16][17][18]. The mandible represents 64% of cases, with 36% occurring in the maxilla [10,11,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations